2017
DOI: 10.1016/j.childyouth.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences among youth aging out of foster care: A latent class analysis

Abstract: Research has demonstrated that youth who age out, or emancipate, from foster care face deleterious outcomes across a variety of domains in early adulthood. This article builds on this knowledge base by investigating the role of adverse childhood experience accumulation and composition on these outcomes. A latent class analysis was performed to identify three subgroups: Complex Adversity, Environmental Adversity, and Lower Adversity. Differences are found amongst the classes in terms of young adult outcomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 59 publications
(54 reference statements)
11
66
0
Order By: Relevance
“…In line with international literature (e.g. Franzén and Vinnerlung 2006;Rebbe et al 2017), the research also shows how pre-care, in-care and after-care experiences shape underlying risk of precarity, as young adults face ongoing challenges including complex family relationships, bereavement, and mental health needs arising from childhood trauma. Through interactions with child welfare and wider systems, those experiences shape the precarity they faceand the support that they receivein navigating transitions through early adulthoods.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In line with international literature (e.g. Franzén and Vinnerlung 2006;Rebbe et al 2017), the research also shows how pre-care, in-care and after-care experiences shape underlying risk of precarity, as young adults face ongoing challenges including complex family relationships, bereavement, and mental health needs arising from childhood trauma. Through interactions with child welfare and wider systems, those experiences shape the precarity they faceand the support that they receivein navigating transitions through early adulthoods.…”
Section: Discussionsupporting
confidence: 78%
“…Researchers have also increasingly highlighted the heterogeneity of care-experienced lives, for example, in modelling relative risk of difficulties in relation to experiences pre-care and whilst in placement (e.g. Fowler et al 2017;Rebbe et al 2017), and in examining the potentially protective affordances of care systems for young people (e.g. Arnau-Sabatés and Gilligan 2015; Sebba et al 2015).…”
Section: Transitions Through Precarious Timesmentioning
confidence: 99%
“…Children with maltreatment histories who are placed into foster care face elevated risks for negative outcomes later in life, with foster care often counteracting the protective factors against poorer health outcomes (Pears, Kim, Fisher, & Yoerger, 2013;Rebbe, Nurius, Ahrens, & Courtney, 2017;Villegas & Pecora, 2012). Moreover, foster care is disproportionately represented by ethnic minorities who often face greater risks due to lower socioeconomic status (Culpin, Stapinski, Miles, Araya, & Joinson, 2015;Villegas & Pecora, 2012).…”
Section: Foster Care Settingsmentioning
confidence: 99%
“…Both identified a low-and a high-risk ACEs class. One of these studies identified two additional classes of household dysfunction/community violence and emotional ACEs (Shin et al 2018), while the other identified community indicators as a separate class (Rebbe et al 2017).…”
Section: Studies Of Interrelated Risks In Adult Samplesmentioning
confidence: 99%